E3 ligase FBXW7 aggravates TMPD-induced systemic lupus erythematosus by promoting cell apoptosis. Issue 12 (December 2018) - Chong, Zhenlu; Bao, Chunjing; He, Jia; Chen, Tianxiao; Zhong, Lijia; Li, Gaopeng; Li, Huanle; Fang, Lutong; Song, Yinjing; Fu, Guoxiang; Yang, Xuyan; Lai, Lihua; et al.
Abstract Systemic lupus erythematosus (SLE) is a systemic autoimmune disease, and the pathogenesis of SLE has not been fully elucidated. The E3 ubiquitin ligaseFBXW7 has been well characterized in cancer as a tumor suppressor that can promote the ubiquitination and subsequent degradation of various oncoproteins; however, the potential role ofFBXW7 in autoimmune diseases is unclear. In the present study, we identified thatFBXW7 is a crucial exacerbating factor for SLE development and progression in a mouse model induced by 2, 6, 10, 14-tetramethylpentadecane (TMPD). Myeloid cell-specificFBXW7 -deficient (Lysm+ FBXW7 f/f ) C57BL/6 mice showed decreased immune complex accumulation, glomerulonephritis, glomerular mesangial cell proliferation, and base-membrane thickness in the kidney. Lysm+ FBXW7 f/f mice produced fewer anti-Sm/RNP and anti-ANA autoantibodies and showed a decreased MHC II expression in B cells. In Lysm+ FBXW7 f/f mice, we observed that cell apoptosis was reduced and that fewer CD11b+ Ly6Chi inflammatory monocytes were recruited to the peritoneal cavity. Consistently, diffuse pulmonary hemorrhage (DPH) was also decreased in Lysm+ FBXW7 f/f mice. Mechanistically, we clarified thatFBXW7 promoted TMPD-induced cell apoptosis by catalyzing MCL1 degradation through K48-linked ubiquitination. Our work revealed thatFBXW7 expression in myeloid cells played a crucial role in TMPD-induced SLE progression in mice, which may provide novel ideas and theoretical support for understanding the pathogenesis of SLE.